The Diagnosis of Lupus Anticoagulants by the Activated Partial Thromboplastin Time - The Central Role of Phosphatidyl Serine - Kelsey, P R; Stevenson, K J; Poller, L (Thrombosis and Haemostasis, 1984)
Liposomes of pure phospholipids were used in a modified APTT test system and the role of phosphatidyl serine (PS) in determining the sensitivity of the test system to the presence of lupus anticoagulants was assessed. Six consecutive patients with lupus anticoagulants and seven haemophiliacs with anticoagulants directed at specific coagulation factors, were studied. Increasing the concentration of phospholipid in the test system markedly reduced the sensitivity to lupus anticoagulants but had marginal effect on the specific factor inhibitors. The same effect was achieved when the content of PS alone was increased in a vehicle liposome of constant composition.The results suggest that the lupus anticoagulants can best be detected by a screening method using an APTT test with a reagent of low PS content. The use of a reagent rich in PS will largely abolish the lupus anticoagulant’s effect on the APTT. An approach using the two different types of reagent may facilitate differentiation of lupus inhibitors from other types of anticoagulant.
Keywords: Lupus anticoagulant; Activated partial thromboplastin time phospholipid; Phosphatidyl serine